Mecanismos de coexistência em espécies com ciclo de vida complexo: um estudo sobre libélulas neotropicais - Pestana, Gabrielle Cristina (Universidade Federal de São Carlos, 2025)
Community ecology aims to understand the maintenance of biodiversity through the mechanisms that enable species to coexist in local communities. The Modern Coexistence Theory (MCT), synthesized by Chesson (2000), is one of the most rigorous frameworks for understanding how competing species persist in the same environment over time. According to this theory, two types of interspecific differences determine stable coexistence: fitness differences and niche differences. Fitness differences are related to variation in species’ competitive and reproductive abilities and, when too large, may lead to the competitive exclusion of lower-fitness species over time. In contrast, mechanisms that increase niche differences (stabilizing mechanisms) promote stronger intraspecific than interspecific competition, reducing resource overlap among species and thus favoring coexistence. For example, reproductive interactions such as territoriality can intensify intraspecific competition, acting as a stabilizing mechanism. Over recent decades, MCT has been widely discussed and applied in both theoretical and empirical studies to investigate how these mechanisms operate across different ecological scenarios. In this context, insects of the order Odonata are excellent models for understanding coexistence mechanisms in species with complex life cycles, as they have an aquatic larval stage and a winged adult stage characterized by diverse reproductive behaviors. Thus, the present thesis aimed to investigate the mechanisms related to intra- and interspecific interactions across different life stages of Neotropical dragonflies. It is structured into three chapters: Chapter I presents an introduction to the main concepts and mechanisms of MCT, along with a scientometric analysis of empirical and theoretical studies published since Chesson (2000), including data on the number of publications by country, taxonomic groups, studied ecosystems, and methodologies employed; Chapter II analyzes the influence of biotic and abiotic factors on the variation in wing spot size (a trait associated with territoriality and male-male sexual competition) in Hetaerina rosea Selys, 1853, both within and among populations. For this purpose, data on intraspecific abundance, total abundance, vegetation cover, and site location were collected from 46 sites in the Central-West region of Brazil. Finally, Chapter III investigates how the effects of intra- and interspecific interactions vary across the life cycle of tropical dragonfly species. The hypothesis tested was that larval-stage competition is predominantly neutral, that is, independent of species identity and driven by total individual density, whereas adult-stage interactions are more intense at the intraspecific level due to reproductive behaviors. To test this, laboratory experiments were conducted using larvae of Acanthagrion (Zygoptera, Coenagrionidae) and Erythrodiplax (Anisoptera, Libellulidae), varying both total abundance and species dominance. Additionally, field observations were carried out to analyze co-occurrence and the frequency of interactions among adults of different Zygoptera and Anisoptera species. In this way, the findings of this dissertation contribute to a deeper understanding of the ecological mechanisms that sustain biodiversity by integrating MCT with empirical studies on Odonata.
Coexistence mechanisms in species with complex life cycles: a study on Neotropical dragonflies and damselflies
Keywords: Biodiversidade; Comunidades; Coexistência; Interações reprodutivas; Odonata; CIENCIAS BIOLOGICAS::ECOLOGIA